PreImplantation factor prevents atherosclerosis via its immunomodulatory effects without affecting serum lipids - Chih Chen, Yung; Rivera, Jennifer; Fitzgerald, Melissa; Hausding, Christian; Ying, Ya-Lan; Wang, Xiaowei; Todorova, Krassimira; Hayrabedyan, Soren; Barnea, Eytan R.; Peter, Karlheinz (Thrombosis and Haemostasis, 2016)
PreImplantation factor (PIF) is a 15-amino acid peptide endogenously secreted by viable embryos, regulating/enabling maternal (host) acceptance/tolerance to the “invading” embryo (allograft) all-while preserving maternal immunity to fight infections. Such attributes make PIF a potential therapeutic agent for chronic inflammatory diseases. We investigated whether PIF’s immunomodulatory properties prevent progression of atherosclerosis in the hyper-cholesterolaemic ApoEdeficient murine model. Male, high-fat diet fed, ApoE-deficient (ApoE-/-) mice were administered either PBS, scrambled PIF (0.3–3 mg/kg) or PIF (0.3–3 mg/kg) for seven weeks. After treatment, PIF (3 mg/kg)-treated ApoE-/- mice displayed significantly reduced atherosclerosis lesion burden in the aortic sinus and aortic arch, without any effect on lipid profile. PIF also caused a significant reduction in infiltration of macrophages, decreased expression of pro-inflammatory adhesion molecules, cytokines and chemokines in the plaque, and reduced circulating IFN-γ levels. PIF preferentially binds to monocytes/neutrophils. In vitro, PIF attenuated monocyte migration (MCP-1-induced chemotaxis assay) and in vivo in LPS peritonitis model. Also PIF prevented leukocyte extravasation (peritonitis thioglycollate-induced model), demonstrating that PIF exerts its effect in part by modulation of monocyte function. Inhibition of the potassium channel KCNAB3 (Kv1.3) and of the insulin degrading enzyme (IDE) was demonstrated as potential mechanism of PIF’s immunomodulatory effects. In conclusion, PIF regulates/lowers inflammation and prevents atherosclerosis development without affecting circulating lipids. Overall our findings establish PIF as a strong immunomodulatory drug candidate for atherosclerosis therapy.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Atherosclerosis; immune cells; ApoE-deficient mice; PreImplantation Factor (PIF); macrophage; immunomodulatory therapy